The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.intell.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A neural analogue of the worst performance rule: Insights from single-trial event-related potentials

Abstract: The worst performance rule is the tendency for participants' slowest reaction times to correlate more with psychometric intelligence than their faster reaction times. Reaction times, however, are influenced by the duration of multiple perceptual, attentional, and motor sub-processes, and it is unclear whether the same pattern exists in these sub-processes as well. We used single-trial event-related potentials to identify whether a worst performance rule pattern could be found in stimulus and response-locked P3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…This is an interesting result in its own right, but in the context of single-trial analysis it is important because it suggests that differences between conditions in terms of latency cannot be attributed to differences in signal-to-noise ratio. Our single-trial analysis technique has identified effects on amplitude in some previous studies (Saville et al 2011 , 2014 ), but not others (Saville et al 2015b , 2016 ) suggesting that it is sensitive to such effects when they are present.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is an interesting result in its own right, but in the context of single-trial analysis it is important because it suggests that differences between conditions in terms of latency cannot be attributed to differences in signal-to-noise ratio. Our single-trial analysis technique has identified effects on amplitude in some previous studies (Saville et al 2011 , 2014 ), but not others (Saville et al 2015b , 2016 ) suggesting that it is sensitive to such effects when they are present.…”
Section: Discussionmentioning
confidence: 73%
“… 2 This is a shorter time window than our previous papers (e.g. Saville et al 2016 ). However, given the relatively simple task, we compared mixed effects models predicting RT using peaks obtained using these windows and the longer windows (250–1000 ms, −375–375 ms).…”
mentioning
confidence: 80%
“…Ratcliff, Thapar and McKoon [43] confirmed the WPR in different tasks only for a group of older adults but not for college students. Similarly, Saville et al [12] did not observe the WPR in n-back-task data from 50 university students. These reports challenge the universality of the WPR and suggest that it may only manifest under specific conditions.…”
Section: The Egm Parameter σ Predicts Gfmentioning
confidence: 89%
“…This regularity, termed the Worst Performance Rule (WPR) by Larson and Alderton [9], has been repeatedly reported for different populations, RT measures, tasks and modalities and does not appear to be a consequence of data artifacts such as outliers, variance restriction or reliability problems (for a review see [10]). Not all studies, however, were able to support the WPR [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our current findings, therefore, the observed relationship between nervous system reliability and attractiveness preferences cannot be explained by physical health, sexual dimorphism or fluctuating asymmetry. One further factor to consider as a potential explanatory variable is psychometric g, which has been shown to be negatively correlated with reaction time variability (Larson & Alderton, 1991;Schmiedek et al, 2007; but see Saville et al, 2016 for a counterexample). Given the necessarily imperfect correlation between reaction time variability and IQ, the effect of g on facial appearance would have to be very large to account for the whole of our effects.…”
Section: Discussionmentioning
confidence: 99%